Regulating the risk of unemployment: national adaptations to post-industrial labour markets in Europe (New York, 2011)
"Regulating the Risk of Unemployment offers a systematic comparative analysis of the recent adaptation of European unemployment protection systems to increasingly post-industrial labour markets. These systems were mainly designed and institutionalized in predominantly industrial economies, characterized by relatively standardized employment relationships and stable career patterns, as well as plentiful employment opportunities even for those with low skills. Over the past two to three decades they have faced the challenge of an accelerating shift to a primarily service-based economy, accompanied by demands for greater flexibility in wages and terms and conditions in low-skill segments of the labour market as well as pressures to maximise labour force participation given the more limited potential for productivity-led growth. The book develops an original framework for analysing adaptive reform in unemployment protection along three discrete dimensions of institutional change, which are termed benefit homogenization, risk re-categorization, and activation. This framework is then used to structure analysis of twenty years of unemployment protection reform in twelve European countries. In addition to mapping reforms along these dimensions, the country studies analyse the political and institutional factors that have shaped national patterns of adaptation. Complementary comparative analyses explore the effects of benefit reforms on the operation of the labour market, assess evolving patterns of working-age benefit dependency, and examine the changing role of active labour market policies in the regulation of the risk of unemployment."